Pengaruh Harga, Promosi Dan Desain Produk Terhadap Keputusan Pembelian Kendaraan Honda Scoopy Pada PT. Kembang Jawa Permai - Ardhea Kusumawati; Edi Murdiyanto; Zaenul Muttaqien (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
This study discusses the influence of price, promotion and product design on the purchase decision of Honda Scoopy vehicles at PT Kembang Jawa Permai. The study aims to explain the influence of price, promotion and product design on the purchase decision of Honda Scoopy vehicles at PT Kembang Jawa Permai. The sample of this study was consumers who bought Honda Scoopy vehicles at PT Kembang Jawa Permai as many as 108 consumers. The sampling technique uses non-probability sampling, namely incidental sampling. The analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression. The results of the study are that there is a positive and significant influence of price on purchasing decisions with a significant value of 0.003 < 0.05. There is a positive and significant influence of promotion on purchasing decisions with a significant value of 0.001 < 0.05. There is a positive and significant influence of product design on purchasing decisions. There is a simultaneous influence of price, promotion and product design on purchasing decisions with a significant value of 0.000 < 0.05.